Does asymmetric information always help entry deterrence? Can it increase welfare? - Pires, Cesaltina (2022)
This paper compares the scenarios of complete and incomplete information in a general model where the incumbent can make a capital investment to deter entry. We show that the informational structure can make an unexpected difference in terms of entry deterrence and efficiency. Although asymmetric information encourages entry deterrence behavior, in some cases it decreases the probability of this behavior inducing no entry and thus promotes competition. In other cases, asymmetric information induces less entry but may lead to higher welfare.